From offer letter to resignation letter - Agarwal, Promila (London : SAGE Publications Ltd, 2017)
Rahul Khanna, Manager of Green Breed Consulting, was frustrated to see a resignation mail from the youngest employee in his team, Ishita Kashyap. Rahul, Ishitas official manager, found it highly unprofessional that a team member had suddenly given her resignation via e-mail while at the clients office without being courteous enough to be available for a face-to-face conversation or at least a telephone call. Ishita wrote the e-mail while working at the clients office located in Rewari, Haryana on a project headed by another manager named Priti Trehan. She had to be at the clients location in Rewari for 20 days. She wrote the e-mail to Rahul on the 2nd day after leaving the New Delhi Office (Head Office) for Rewari.GBC had a policy requiring 30-days notice in cases of resignation, which meant that officially Ishita could leave GBC within ten days once she was back from Rewari. Rahul knew that Ishita had deliberately written a resignation mail from the clients office so that she could avoid him. Rahul felt that Ishita could have informed him about her resignation before she left for Rewari.
Originally published: Agarwal, P. (2014). From offer letter to resignation letter. P&IR0228. Ahmedabad: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Green Breed Consulting; Personnel management -- India; Employee retention -- India; Exit interviewing -- India